Benign uptake of 18F-fluorodeoxyglucose in the gallbladder on positron emission tomography-computed tomography - Hussain, Riffat; Nausheen, Sadaf; Ahmed, Naveed; Mahmood, Tariq (World Journal of Nuclear Medicine, 2020)
18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) has been established as the indisputable tool in the oncological arena to diagnose, stage/restage, and report treatment response for various tumor malignancies. FDG uptake mostly identifies pathological uptake in oncological scans with the tracer on PET studies; however, benign uptakes are also commonly seen. Reported here is a benign case of increased uptake of the FDG on a PET with computed tomography scan in the gallbladder (GB) of a patient being screened for a known carcinoma breast. The benign accumulation of the tracer is seen in the GB to various degrees and this phenomenon may occur as a result of FDG excretion into the bile. When interpreting clinical PET images, recognition of this phenomenon is important to avoid misdiagnosing physiological GB FDG uptake as pathological so as to avoid misinterpretations of the findings.
Keywords: Benign uptake; 18F-fluorodeoxyglucose; gallbladder; positron emission tomography-computed tomography